2013
DOI: 10.1590/s1516-05722013000300010
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização e atividade antibacteriana de óleos essenciais de plantas condimentares e medicinais contra Staphylococcus aureus e Escherichia coli

Abstract: RESUMO:Os óleos essenciais são metabólitos secundários vegetais com propriedades biológicas diferenciadas, dentre elas a atividade contra microrganismos, sendo de importante interesse para a indústria de alimentos. As concentrações mínimas inibitórias (CMI) desses óleos para diversas bactérias devem ser determinadas. As CMI variam de acordo com o óleo utilizado, dos compostos majoritários e do tipo de bactéria. Nesta pesquisa, os óleos essenciais das plantas Satureja montana L., Cymbopogon nardus L. e Citrus l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
1
3
0
4
Order By: Relevance
“…In a study the authors mentioned that the cells adhere better on hydrophilic surfaces (stainless steel, glass) than on hydrophobic surfaces (rubber and plastics) (STEPANOVIC´et al, 2000). Several other bacteria readily form biofilms on stainless steel surface (MILLEZI et al, 2012). In the present study, it was found that 24 hours was sufficient for the formation of biofilms of E. coli and S. aureus on stainless steel coupons.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…In a study the authors mentioned that the cells adhere better on hydrophilic surfaces (stainless steel, glass) than on hydrophobic surfaces (rubber and plastics) (STEPANOVIC´et al, 2000). Several other bacteria readily form biofilms on stainless steel surface (MILLEZI et al, 2012). In the present study, it was found that 24 hours was sufficient for the formation of biofilms of E. coli and S. aureus on stainless steel coupons.…”
Section: Resultssupporting
confidence: 52%
“…Escherichia coli is one of the most versatile microorganisms reported in nature. Due to frequent precarious hygienic sanitary food production, it is common to observe them contaminating E. coli, as an aggravating factor, the bacteria form biofilms with ease in stainless steel surface (FROZI et al, 2017), polystyrene (MILLEZI et al, 2016) and polipropilene Millezi et al (MILLEZI et al, 2012). Staphylococcus aureus is a Gram-positive organism, mesophyll; however, studies showed that it can grow in a wide range of temperatures.…”
Section: Introdutionmentioning
confidence: 99%
“…Essential oils and their compounds are known to be active against a wide variety of microorganisms, including Gram-positive and Gram-negative bacteria 7,8,13,16 in both planktonic form 24,26 and biofilm 25,27,30 . Bacteria in biofilm mode of growth have been much more resistant to antibiotics than their planktonic counterparts 21,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Nem todas as bactérias da família Enterobacteraceae são capazes de causar doenças quando em contato com o organismo. Algumas precisam da presença de determinados parasitas, mas mesmo assim é necessárias boas práticas de higienização de alimentos, evitar o consumo de carnes malcozidas e de água não tratada a fim de evitar o possível contágio de Enterobactérias (ABREU e CABRAL, 2005;MILLEZI et al, 2013).…”
Section: Introductionunclassified